Varieties of an Atheist Public in a Digital Age: The Politics of Recognition and the Recognition of Politics - Laughlin, Jack C. (Journal of religion, media and digital culture, 2016)
With the rise of atheism as a cause célèbre in the last decade or more, media and others have offered many interpretations for the apparent growth of nonbelief, ranging from the apocalyptic to the utopian. Many cite the Internet as a major contributing factor to this growth; undoubtedly new media have provided atheism with greater visibility. In this article it is argued that atheism as an Internet phenomenon ought to be understood less as the manifestation of a social fact and more as the discursive constitution of one or more publics in Michael Warner’s sense of the term. To this end, the article draws attention to a body of data that has received limited attention in scholarship to date, namely the blogs of some notable atheists. These are limited to blogs originating in the United States, and especially those by authors who identify as ‘progressive’. Thus, the conclusions drawn are not imagined to apply outside that context, nor are the sources employed considered to be representative of American atheism. But these limitations present no bar to the analysis of the particular discursive practices of the authors in question. Following Warner, virtual atheism as a public or publics has little capacity for agency: even if its growth as a social fact is true, and even as it develops agendas for social change, it is neither discursively or substantively robust enough to challenge any aspect of the contemporary neo-liberal order.